(IN)VISIBLE TRACES: THE PRESENCE OF THE RECENT PAST IN THE URBAN LANDSCAPE OF SARAJEVO - Natalia Otrishchenko (Місто: історія, культура, суспільство, 2018)
The author reflects on her observations during the summer school ‘History Takes Place – Dynamics of Urban Change.’ She discusses the number of locations, which embodied or recalled the memories of war and siege of the city, both those that remained from 1992-95 and those newly created. Based on the concept of the production of space, the article outlines the specifics of interventions into urban landscape with either monuments or alternative forms of commemoration.